2018
DOI: 10.3390/w10030273
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Operation of Hydropower Reservoirs under Climate Change: The Case of Tekeze Reservoir, Eastern Nile

Abstract: Abstract:Optimal operation of reservoirs is very essential for water resource planning and management, but it is very challenging and complicated when dealing with climate change impacts. The objective of this paper was to assess existing and future hydropower operation at the Tekeze reservoir in the face of climate change. In this study, a calibrated and validated Soil and Water Assessment Tool (SWAT) was used to model runoff inflow into the Tekeze hydropower reservoir under present and future climate scenari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 57 publications
(80 reference statements)
3
21
0
Order By: Relevance
“…They used a combination of different regional climate model, and they showed potential increase in precipitation that my lead to an increase in energy production. Abera et al [60] in the same basin found also a similar pattern in precipitation and temperature increase, with consequent increase of discharge. They find a potential increase of the water volume stored in the reservoir, leading to an increase in production, similarly to what we found here for the GERD reservoir.…”
Section: Limitations and Outlookssupporting
confidence: 55%
“…They used a combination of different regional climate model, and they showed potential increase in precipitation that my lead to an increase in energy production. Abera et al [60] in the same basin found also a similar pattern in precipitation and temperature increase, with consequent increase of discharge. They find a potential increase of the water volume stored in the reservoir, leading to an increase in production, similarly to what we found here for the GERD reservoir.…”
Section: Limitations and Outlookssupporting
confidence: 55%
“…According to , the suspended sediment response to climate change generally followed the patterns of simulated changes in streamflow. Climate change can also affect future reservoir planning and management [18]. The volume variability of lake is more responsive to extreme climate events than to other anthropogenic factors [7].…”
mentioning
confidence: 99%
“…Abera, Asfaw, Engida, and Melesse () studied optimal operation (using HEC‐ResPRM model) under climate change for the Tekeze (hydropower) reservoir on the Eastern Nile (294,040 km 2 in Ethiopia and Sudan, see also Kim & Kaluarachchi, ). Outputs of the Downscaling Experiment over African domain (CORDEX‐Africa) under RCP4.5 and RCP8.5 resulted into an increase of power storage potential up to +25% and +30% under RCP4.5 and RCP8.5 until 2100, in response to an increase of monthly inflows except in May to June.…”
Section: Discussionmentioning
confidence: 99%